2007
DOI: 10.1002/ejic.200600619
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Control of the Rotational Barrier in η2‐Alkyne‐1‐thio Complexes

Abstract: A family of thio‐alkyne complexes [Tp′Mo(CO)(L)(BnSC2S)] {Bn = benzyl, Tp′ = hydrotris(3,5‐dimethylpyrazolyl)borate, L = carbonyl (2), 2,6‐dimethylphenyl isocyanide (7), tert‐butyl isocyanide (8), 4‐(dimethylamino)pyridine (9)} was prepared by reductive removal of a benzyl group in the corresponding bis(benzylthio)acetylene complexes [Tp′Mo(CO)(L)(BnSC2SBn)](PF6) (1‐PF6, 4‐PF6, 5‐PF6 and 6‐PF6). All complexes were characterized by IR, 1H, 13C spectroscopy and cyclic voltammetry. X‐ray diffraction studies of 5‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…However, at low temperatures we encountered serious solubility problems. We have recently shown that weaker π-acidic ligands like isocyanides in the alkyne complex distinctively lower the rotational barrier of the alkyne . Consistently, a single alkyne carbon resonance was observed in the room-temperature 13 C NMR spectrum of 6a and 6b .…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…However, at low temperatures we encountered serious solubility problems. We have recently shown that weaker π-acidic ligands like isocyanides in the alkyne complex distinctively lower the rotational barrier of the alkyne . Consistently, a single alkyne carbon resonance was observed in the room-temperature 13 C NMR spectrum of 6a and 6b .…”
Section: Resultsmentioning
confidence: 57%
“…The C1−S1 and C2−S2 bond distances of 1.668(8) and 1.670(7) Å are equal within the margin of error. The difference in the Mo−C1 and Mo−C2 bond distances (2.056(8) vs 2.108(7) Å) reflects contributions of resonance structure B (see Scheme ), but it is smaller compared with the differences found in the neutral complexes 2a / 2b / 2c . , The bend-back angles of 143.8° (C1−C2−S2) and 138.3° (C2−C1−S1), respectively, give rise to an intramolecular S1−S2 distance of 3.899 Å, which is far too large for a chelate coordination.
1 Molecular structure of the anion 3c - ; hydrogen atoms are omitted; 50% ellipsoid probability.
2 Synthesis of Metalla-Acetylendithiolato Complexes
2 Molecular structure of 4b ; hydrogen atoms are omitted; 50% ellipsoid probability.
…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In 2011 a double η 2 ‐S, C coordination mode ( B ) was reported, disclosed in a dinuclear Co complex of ethenedithione (S=C=C=S) 5. The alternative η 2 ‐C, C′ mode ( C ) is regularly observed in well‐understood intermediate products on the path to acdt 2– complexes,6 while first examples were originally described by Hill 7. The third type, an end‐on η 1 ‐S motif ( D ) was reported by Behrens , whose studies involve the coordination behavior of certain stable and therefore sterically encumbered thioketenes 8…”
Section: Introductionmentioning
confidence: 99%